The Impact of Social Capital on the Immigrants’ Integration alongside the Rural-Urban Continuum: Evidence from Greece - Liltsi, Petroula; Michailidis , Anastasios; Loizou, Efstratios; Chatzitheodoridis, Fotios (Asian Journal of Agriculture and Rural Development, 2020)
This paper aims to develop methodological tools which will contribute to estimate the impact of social capital on the integration of immigrants alongside the Rural-Urban Continuum of the Prefecture of Thessaloniki. The importance of this paper derives from the current debate in this respect with insufficient infrastructures for smooth integration of immigrants into societies and the need to develop an immigration policy which emphasizes the strengthening of policies on the development of multiculturalism and social cohesion. For this purpose, a survey was carried out in 607 residents of the Prefecture of Thessaloniki during the period June to November 2016. The data collected and other information were utilized according to simple descriptive or multivariate statistical analyzes as well as qualitative techniques. Based on the descriptive statistical analyzes the paper concluded that “social capital” is key component in the structure of the relationship between natives and immigrants and according to the results of CatReg models the main reason, which has a positive impact on the "integration" of immigrants, is their participation in community activities.